2015
DOI: 10.1007/s10533-015-0123-2
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen addition changes grassland soil organic matter decomposition

Abstract: Humans have dramatically increased the deposition and availability of nutrients, such as nitrogen (N), worldwide. Soil organic matter (SOM) is a significant global reservoir of carbon (C); however, the effects of N enrichment on this large, heterogeneous C stock are unclear. Nitrogen has variable effects on the biological, chemical, and physical factors that determine SOM pool mean residence time; consequently, we predicted that N enrichment would have distinct effects on SOM pools, including the pool that is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
119
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(136 citation statements)
references
References 81 publications
14
119
3
Order By: Relevance
“…This also agrees with the findings from a long-term N fertilization experiment in meadow communities of alpine tundra, which suggest that under chronic N addition detritus plant material can move directly into stabilized mineral-associated organic matter pools (Neff et al 2002). Finally, our finding agrees with the observation that N fertilization can contribute to C accumulation and stabilization in small mineral-associated soil aggregates (Riggs et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…This also agrees with the findings from a long-term N fertilization experiment in meadow communities of alpine tundra, which suggest that under chronic N addition detritus plant material can move directly into stabilized mineral-associated organic matter pools (Neff et al 2002). Finally, our finding agrees with the observation that N fertilization can contribute to C accumulation and stabilization in small mineral-associated soil aggregates (Riggs et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, we interpret CO 2 production at the end of the incubation to be from a recalcitrant pool. It is possible to use microbial respiration data to model the size and decay rates of soil carbon pools (see Riggs et al 2015), but our analysis focuses on differences in soil respiration rates and the decay of these rates during the incubation period. We used Akaike's information criterion to identify the best (lowest AICc) and other plausible models (DAICc \ 2) for each sample.…”
Section: Soil Carbon Quality Across Landscape Age and Climate Gradientsmentioning
confidence: 99%
“…Soil organic carbon (SOC), which is the largest carbon reservoir in the terrestrial biosphere, contains two to four times the amount of carbon in the atmosphere. Consequently, either positive or negative changes of soil carbon storage, in response to N deposition, could lead to significant alteration in the carbon dioxide (CO 2 ) concentration of atmosphere (Riggs et al, 2015;Zak et al, 2017), and thus have implications for future global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that soil N input has the potential to decrease microbial decomposition of SOC and thereby increase soil carbon storage (Ramirez et al, 2012;Zhou et al, 2014;Riggs et al, 2015). Although this negative effect of N input on microbial decomposition of SOC seems paradoxical since the increased input of plant litter and root exudates induced by N enrichment may increase carbon availability to microbes (Liu and Greaver, 2010), a number of microbial mechanisms have been proposed to explain why microbial decomposition of SOC decreases with N addition (Riggs and Hobbie, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation